Pancasila Era Orde Lama, Orde Baru dan Reformasi - Ahmad Muhamad Mustain Nasoha; Ashfiyah Nur Atqiya; Nauroh Aisy Salsabila; Naella Alfi Syarifah; Sisil Larassati; Mahmud Isma’il Marzuki (International Forum of Researchers and Lecturers, 2024)
This study aims to examine the role and implementation of Pancasila in three periods of government in Indonesia: Old Order, New Order, and Reformasi. Pancasila, as a state ideology, has undergone various changes in interpretation and application in accordance with the political and social dynamics that occur in each era. Under Soekarno's leadership in the Old Order, Pancasila was used as a unifying tool in the context of ideological pluralism, but faced internal and external challenges that threatened national stability. During the New Order period, Pancasila was used as a single principle used to strengthen political legitimacy, but it was often misused to silence criticism and opposition. The reforms brought greater political freedom and a more inclusive interpretation of Pancasila, but still faced challenges in overcoming radicalization, intolerance, and social disparities. This research concludes that although Pancasila remains relevant as the basis of the state, efforts are needed to actualize its values to suit the challenges of the times.